2015
DOI: 10.2337/dc14-1873
|View full text |Cite
|
Sign up to set email alerts
|

Serum Mannose-Binding Lectin Is a Strong Biomarker of Diabetic Retinopathy in Chinese Patients With Diabetes

Abstract: OBJECTIVEInflammation and complement activation initiated by mannose-binding lectin (MBL) may be implicated in the pathogenesis of diabetic vascular complications. We investigated serum MBL levels in patients with diabetes with and without diabetic retinopathy (DR). RESEARCH DESIGN AND METHODSSerum MBL levels were determined in 348 patients with diabetes and in 100 healthy control subjects. The prediction value of MBL was compared with diabetes duration, hs-CRP, and other known predictors. Multivariate analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 42 publications
0
11
0
2
Order By: Relevance
“…Many studies showed that a low or high serum MBL level is involved in several immune mediated diseases (e.g., RA, Crohn’s disease, Sjögren disease and diabetic retinopathy 2224 ). Immune defense function of MBL is associated with its serum level and oligomeric type 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies showed that a low or high serum MBL level is involved in several immune mediated diseases (e.g., RA, Crohn’s disease, Sjögren disease and diabetic retinopathy 2224 ). Immune defense function of MBL is associated with its serum level and oligomeric type 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic measurements reflect an individual's endogenous biochemical processes and environmental exposures [1,2]. Many circulating lipids, lipoproteins and metabolites have been previously implicated in the development of cardiovascular disease (CVD) [3][4][5][6] or used as biomarkers for disease diagnosis or prognosis [7,8]. Understanding the genetic influence on circulating levels of these metabolic biomarkers can help us gain insight into the biological processes regulating these traits, lead to improved aetiological understanding of CVD and identify novel potential therapeutic drug targets.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic measurements reflect an individual’s endogenous biochemical processes and environmental exposures [1,2]. Many circulating lipids, lipoproteins and metabolites have been previously implicated in the development of cardiovascular disease (CVD) [3-6] or used as biomarkers for disease diagnosis or prognosis [7,8]. Understanding the genetic influence on circulating levels of these metabolic biomarkers can help us gain insight into the biological processes regulating these traits, lead to improved aetiological understanding of CVD and identify novel potential therapeutic drug targets.…”
Section: Introductionmentioning
confidence: 99%